On the Fisher-Konieczny index of price changes synchronization - Dias, D. A. (2022)
This note provides a structural interpretation for the index of price changes synchronization proposed by Fisher and Konieczny (2000, Economics Letters, 68, 271-277) and shows that it can be used to test the hypothesis of uniform staggering